2020
DOI: 10.1016/j.jinf.2020.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of older patients: The experience of a geriatric short-stay unit dedicated to patients with COVID-19 in France

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website.Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre -including this research content -immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 9 publications
5
63
0
4
Order By: Relevance
“…The laboratory findings of 1194 patients were reported [10][11][12][13][14][15][16][17][18]24,[26][27][28]. The majority of the results were presented as median (IQR), except for Cheng B et al as mean and SD [13].…”
Section: Laboratory Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The laboratory findings of 1194 patients were reported [10][11][12][13][14][15][16][17][18]24,[26][27][28]. The majority of the results were presented as median (IQR), except for Cheng B et al as mean and SD [13].…”
Section: Laboratory Findingsmentioning
confidence: 99%
“…Complications Despite only 9 studies reporting complications, the results pertained to 3241 patients [10,12,[15][16][17][18]24,26,29]. Renal impairment/injury was the most prominent complication with an incidence rate of 25.7%.…”
Section: Aging and Disease • Volume 11 Number 4 August 2020 999mentioning
confidence: 99%
“…A fall was the first sign of the infection for more than a quarter of our patients. 32 Guan et al reported that thrombopenia and lymphopenia have been frequently observed in adult patients with COVID-19, but Godaert et al reported lymphopenia was more frequent than thrombopenia or leukopenia in their study. 32,33 Evaluating the molecular pathogenesis and the role of the immune system in modulating symptoms it can be assumed that susceptibility of COVID-19 to older adults is more.…”
Section: Symptoms Of Covid-19 and Its Effect On Geriatric Individualsmentioning
confidence: 73%
“…32 Guan et al reported that thrombopenia and lymphopenia have been frequently observed in adult patients with COVID-19, but Godaert et al reported lymphopenia was more frequent than thrombopenia or leukopenia in their study. 32,33 Evaluating the molecular pathogenesis and the role of the immune system in modulating symptoms it can be assumed that susceptibility of COVID-19 to older adults is more. There are various contributing factors for poor health outcomes and these include the physiologic changes of aging; multiple comorbid conditions such as heart and lung disease, diabetes, and dementia; and associated immunosuppressive disorders.…”
Section: Symptoms Of Covid-19 and Its Effect On Geriatric Individualsmentioning
confidence: 73%
See 1 more Smart Citation